2022
DOI: 10.1186/s10020-022-00527-z
|View full text |Cite
|
Sign up to set email alerts
|

Role of miRNA dysregulation in sepsis

Abstract: Background Sepsis is defined as a state of multisystem organ dysfunction secondary to a dysregulated host response to infection and causes millions of deaths worldwide annually. Novel ways to counteract this disease are needed and such tools may be heralded by a detailed understanding of its molecular pathogenesis. MiRNAs are small RNA molecules that target mRNAs to inhibit or degrade their translation and have important roles in several disease processes including sepsis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 155 publications
0
22
0
1
Order By: Relevance
“…This may be mediated by miRNAs. miRNAs are associated with the pathophysiological process of many diseases ( Formosa et al, 2022 ) and are involved in the occurrence and development of SIC ( Beltrán-García et al, 2021 ). We therefore built a TF-miRNA-hub gene network depending on the shared dataset and published literature.…”
Section: Discussionmentioning
confidence: 99%
“…This may be mediated by miRNAs. miRNAs are associated with the pathophysiological process of many diseases ( Formosa et al, 2022 ) and are involved in the occurrence and development of SIC ( Beltrán-García et al, 2021 ). We therefore built a TF-miRNA-hub gene network depending on the shared dataset and published literature.…”
Section: Discussionmentioning
confidence: 99%
“…MiRNAs can bind to the 3′‐UTR of target mRNAs resulting in the mRNA degradation and inhibition of the mRNA protein translation 39 . Further investigations were performed to elucidate the downstream mechanism of miR‐579‐3p.…”
Section: Discussionmentioning
confidence: 99%
“…MiRNAs can bind to the 3 0 -UTR of target mRNAs resulting in the mRNA degradation and inhibition of the mRNA protein translation. 39 Further investigations were performed to elucidate the downstream mechanism of miR-579-3p. Bioinformatics and dual luciferase analysis confirmed that ZEB2, a zinc-finger transcription factor, was negatively correlated with miR-579-3p expression in patients with septic AKI.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with VS develop a systemic inflammatory response leading to endothelial dysregulation, systemic vasodilation refractory to vasopressors, hypotension and progressive death 13 . Despite the lack of information regarding miRNAs in VS, some inflammatory diseases, such as sepsis 14 , systemic inflammatory response syndrome 15 , and sepsis-related acute lung injury 16 , that have a similar mechanism as VS, were studied and also show a correlation with dysregulation levels of hsa-miR-30d-5p in body fluids [15][16][17] . Here we show that in comparison to healthy controls, the levels of www.nature.com/scientificreports/ miR-30d-5p are increased in whole blood of VS patients, suggesting a possible anti-inflammatory role for this miRNA 17 .…”
Section: Discussionmentioning
confidence: 99%